The U.S. Supreme Court and the Free Exercise Clause: Are Standards of Adjudication Possible? - Sheffer, Martin S. (A journal of church and state, 1981)
Martin S. Sheffer; The U.S. Supreme Court and the Free Exercise Clause: Are Standards of Adjudication Possible?, Journal of Church and State, Volume 23, Issue 3